The Dynamics of Political Violence and Demonstrations in Somalia: Evidence from ACLED data - Yusuf, Mohamud Isse (Technium Social Sciences Journal, 2025)
Background: Political violence primarily serves a symbolic purpose, with its cultural and emotional impacts outweighing the physical destruction it causes. Research on social movements has highlighted the significance of cultural dynamics in the emergence of political violence, examining both the internal and external aspects of radical groups. Demonstrations serve as a crucial negotiation tool for those challenging authoritarian regimes. Conflict is dynamic, adapting as parties react to each other’s actions, shifts in power, and external interventions. Objective of the study: The study was guided by three objectives, which included A) to compare regional variations in the number of political events and associated fatalities in Somalia from January to November 2024 using ACLED data, B) to assess the correlation between the number of political events and the number of fatalities in Somalia using ACLED data and C) to examine the effect of the number of political events on the number of fatalities in Somalia using ACLED data. Methodology: This study utilized retrospective data, utilizing the Armed Conflict Location and Event Data (ACLED) collected from Somalia between January and November 2024. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS) software and Excel spreadsheets to generate percentages, charts, tables, and statistical conclusions pertinent to the study objectives. The researcher applied descriptive analysis to summarize statistics and employed inferential analysis, including correlation and regression analysis, to evaluate the association and effect of the number of political events on the number of fatalities in Somalia. Result: The study identified a correlation coefficient of 0.109 between the number of political events and the number of fatalities. This indicates a very weak positive correlation, suggesting a slight tendency for fatalities to increase as the number of political events rises. The p-value (significance level) for this correlation is 0.750. The findings of the study also reveal that regional variations elucidate the complex interactions between political events and fatalities. Understanding these dynamics is crucial for policymakers and researchers, as it highlights the need for tailored approaches in conflict resolution and governance. Recommendation: The study recommends that, given the findings from both regression and correlation analyses, political events alone do not sufficiently account for conflict-related fatalities. Therefore, it is advised that national planners and humanitarian organizations implement comprehensive risk assessments. Additionally, the study underscores the necessity of disaggregating conflict data by region. It is crucial for future research and programs to persist in analyzing data at sub-national levels to discern significant trends and enable geographically specific interventions. Conclusion: In conclusion, this study underscores the importance of transcending the simplistic assumption that increased political activity inherently leads to heightened violence. It advocates for the implementation of context-specific approaches, which consider regional dynamics, local governance structures, traditional conflict resolution methods, and other essential socio-political factors.